Housing Need and Deficit in the City of Fallujah in Iraq for 2023 - Suleiman, Naba; Ali , Bilal (Al-Adab Journal, 2025)
Objective: The study aims to identify the factors that caused the increase in housing need in the city of Fallujah, and to estimate the need, stock, and housing deficit therein.Methodology: The survey approach was used to identify the factors that caused the increase in housing need in the city, and the quantitative approach by applying a set of equations with the aim of estimating the housing need and the housing deficit.Results: The study included three topics. The first presents the factors that led to an increase in housing need. The second shows estimating housing need, the housing stock and the housing deficit.  Third indicates the estimating future housing need. The study concluded that the increase in housing need in the city of Fallujah resulted from a group of factors:These are factors related to population, factors related to the characteristics of housing units, and factors related to some housing policies. The study also found that the housing need in the city in 2023 is estimated at (4216) housing units, while the uninhabitable stock reached (1562) housing units compared to (32883) inhabitable housing units, while the housing deficit reached (5778) housing units.Recommendations: The research recommends the necessity of working on an urban renewal policy for dilapidated and old housing units in the city, through the renovation and maintenance of old housing units, so that they are part of the housing stock for families with limited income.